“Why do I do what I do?” The meaning of work from the perspective of social pedagogues as informal leaders in all-day schools - Scholian, Andrea; Kappler, Christa; Stohler, Renate; Schuler Braunschweig, Patricia (Frontiers in Education, 2025)
The number of all-day schools in Switzerland is growing fast. However, the development of new guidelines and regulations in this field is lagging. In their unique position, the professionals not only execute but also define and lead educational practices in all-day schools. In the present study, problem-based group interviews were conducted with extended educational staff in schools in urban Switzerland to review their educational practices and to uncover the meaning they ascribe to their work. The interviews provided insights into professional beliefs and attitudes and were analyzed using thematic analysis. The data revealed two areas of tension in which social pedagogues operate: on the one hand between “fulfilling individual needs and serving a large number of children” and on the other hand between “providing spaces for experience and building trusting and close relationships with children.” Different ways of shaping the work can be determined, depending on the professional background and qualification of the staff. In the future, it is essential to make the work of staff in all-day schools visible and to highlight the challenges in dealing with different demands in the hope that a coherent attitude toward their work will emerge.